2013
DOI: 10.1177/1071100713487724
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Forces in Flexor Hallucis Longus Versus Flexor Digitorum Longus Transfer in Adult Acquired Flatfoot Deformity

Abstract: This cadaveric study shows that the FHL is more biomechanically suitable for tibialis posterior tendon insufficiency than the FDL, which may be a basis for a study to investigate whether it is superior in a clinical situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Several reports have given successful outcomes with the usage of FHL tendon grafts, especially in Achilles tendon repair surgeries. 25 , 26 Besides, Spratley et al 27 proposed using FHL tendon grafts instead of FDL tendon grafts in posterior tibial tendon dysfunction. However, nerve injuries or toe deformities after FHL tendon transfers were also reported, particularly while harvesting this tendon distal to the MKH.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have given successful outcomes with the usage of FHL tendon grafts, especially in Achilles tendon repair surgeries. 25 , 26 Besides, Spratley et al 27 proposed using FHL tendon grafts instead of FDL tendon grafts in posterior tibial tendon dysfunction. However, nerve injuries or toe deformities after FHL tendon transfers were also reported, particularly while harvesting this tendon distal to the MKH.…”
Section: Discussionmentioning
confidence: 99%
“…14,21,52,56,61 FDL may be favored because the tendon courses adjacent to the PTT (facilitating the approach), it is straightforward to locate anatomically, and its function is more expendable than great toe function; however, it is biomechanically weaker than the FHL. 8,52,109 The FHL has a larger size and was superior in a biomechanical study, although this has not been demonstrated in clinical scenarios. 8,109 In either case, tendon transfer alone is weak biomechanically and does not change the medial longitudinal arch height or hindfoot valgus deformity.…”
Section: Tendon Transfermentioning
confidence: 98%
“…The FDL and FHL are identified distal to the knot of Henry and tenodesed distally to the knot with a nonabsorbable suture to preserve some flexion force. 109 The FDL is then transected proximal to this location but distal to the knot of Henry. This allows sufficient length for the FDL tendon to be transferred to the navicular, where it is secured through a drill hole.…”
Section: Authors' Preferred Operative Treatmentmentioning
confidence: 99%
“…In these cases, each procedure specifically addresses different portions of the deformity. In almost every case, augmentation of the PTT is performed with either the Flexor Digitorum Longus (FDL) or the Flexor Hallucis Longus (FHL) with a FHL tendon transfer growing in occurrence . From there, the choice is whether or not to use a hindfoot procedure with the Medializing Calcaneal Osteotomy (MCO), a lateral column lengthening (LCL) procedure with the Evans Osteotomy, Calcaneocuboid Distraction Arthrodesis (CCDA), or the Z Osteotomy, or a combination of both hindfoot and a single LCL procedure …”
mentioning
confidence: 99%